Russian Wedding Songs of Udmurt Republic: Kinetic Aspect - S. V. Tolkachova (Научный диалог, 2017)
The article is devoted to peculiarities of the kinetic aspect of the performance of wedding songs. Based on Russian song folklore of southern and central districts of the Udmurt Republic, the author identified the ritual significance of movements that accompany the performance of wedding songs. The dialectal names for wedding songs are given. Summarized data on types of movements typical for different genres of wedding musical folklore. It is concluded that they are determined by the ethnographic context. The fact of perception by the informants of description of the action from the song text as the reality of the wedding ceremony is discovered. The examples of polyphonic layers of genres of wedding song folklore are demonstrated. The author shows that verbal, acoustic, musical, kinetic codes of ritual can have a different meaning in the performance of a number of wedding songs. It is noted that the kinetics of the performance of wedding songs has brightly expressed game nature. Verbal and kinetic parallels in the Russian wedding and calendar folk songs of the Udmurt Republic are analyzed. The author comes to the conclusion that the combination of duplicating codes in the wedding ritual - kinetic, verbal, musical and other - have reinforced the sacred significance of the wedding ceremony. Semantic polyphony of codes of ritual gave the episodes of the wedding ceremony totality and one-time interaction between “this” and “other” worlds.